Queer Chicana/Latina Feminisms, World-Making and Latinx Geographies: Una Plática entre Nosotras - Cahuas, Madelaine; Muñoz, Lorena (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2024)
This paper explores how pláticas can serve as a critical Chicanx/Latinx feminist methodology in geography, not only informing the research we do, but how we teach, mentor, organize and sustain ourselves in relation to our communities. Bridging Chicana/Latina feminist theory and feminist geographies literature, we provide a context for our plática, share our academic journeys, and delve into Lorena Muñoz’ path-breaking contributions spatializing queer Chicana/Latina feminisms, theorizing Latinx world-making, and advancing the subdiscipline of Latinx geographies. We consider how pláticas incite possibilities for fostering more caring, equitable relationships inside and outside the academy.